2024
DOI: 10.1002/cncr.35286
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal quality of life after sublobar resection and stereotactic body radiation therapy for early‐stage non–small cell lung cancer

Juan P. Wisnivesky,
Jeremy Mudd,
Kimberly Stone
et al.

Abstract: BackgroundMany patients with early‐stage lung cancer are not candidates for lobectomy because of various factors, with treatment options including sublobar resection or stereotactic body radiation therapy (SBRT). Limited information exists regarding patient‐centered outcomes after these treatments.MethodsSubjects with stage I–IIA non–small cell lung cancer (NSCLC) at high risk for lobectomy who underwent treatment with sublobar resection or SBRT were recruited from five medical centers. Quality of life (QOL) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Lastly, another study by Iguchi et al utilizing RFA found an OS and CSS of 93.3% and 100%, respectively, at 1 and 5 years [ 60 ]. Comparing the QoL of segmentectomy with SBRT has also been studied using the Short Form 8 (SF-8), for physical and mental health, and Functional Assessment of Cancer Therapy-Lung (FACT-L) surveys [ 61 ]. Patients reported better QoL immediately postop with SBRT but no significant difference between the two in long-term QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, another study by Iguchi et al utilizing RFA found an OS and CSS of 93.3% and 100%, respectively, at 1 and 5 years [ 60 ]. Comparing the QoL of segmentectomy with SBRT has also been studied using the Short Form 8 (SF-8), for physical and mental health, and Functional Assessment of Cancer Therapy-Lung (FACT-L) surveys [ 61 ]. Patients reported better QoL immediately postop with SBRT but no significant difference between the two in long-term QoL.…”
Section: Discussionmentioning
confidence: 99%